Cathepsin L-like protease can regulate the process of metamorphosis and fat body dissociation in Antheraea pernyi. (January 2018) - Sun, Yu-Xuan; Tang, Lin; Wang, Pei; Abbas, Muhammad Nadeem; Tian, Ji-Wu; Zhu, Bao-Jian; Liu, Chao-Liang
Abstract: Cathepsins are a group of protease, located in lysosome and play a vital role in physiological process. Here, we reported cathepsin L-like protease ( Ap-cathL ), which contained an open reading frame of 1155 bp and encoding 385 amino acid residues protein. The I29 inhibitor domain and peptidase C1A (clan CA of cysteine proteases, papain family C1 subfamily) putative conserved domains were detected in Ap-cathL. Quantitative real-time PCR (qRT-PCR) analysis revealed that Ap-cathL highly expressed in the fat body and midgut. The high expression during the molting stage, pupal stage and following 20E (20-hydroxyecdysone) treatment indicated that it maybe involved in the process of molting and metamorphosis. In addition, depletion of Ap-cathL influenced the expression of apoptosis pathway related genes. The protease inhibitor and RNA interference experiments showed that Ap-cathL was involved in the fat body dissociation of A. pernyi . These results suggest that Ap-cathL may involve in the process of metamorphosis and fat body dissociation of A. pernyi . Highlights: A cathepsin L-like protease (Ap-cathL) was first characterized from A. pernyi. The spatial and temporal expression profiles of Ap-cathL were investigated. 20E (molting hormone) induces Ap-cathL expression in the fat body. Ap-cathL RNAi influenced the expression of apoptosis-related genes. Ap-cathL functions in the fat body dissociation via inhibitor and RNAi experiments.